Pengaruh Collection Period Variance dan Kebijakan Modal Kerja terhadap Profitabilitas Pada Perusahaan Syariah Sektor Properti dan Konstruksi di ISSI Periode 2015-2024 - Dien Azzizah Azzahra Farhani; Mochamad Edman Syarief; Setiawan; Ira Novianty (ITB AAS INDONESIA Surakarta, 2026)
This study aims to examine the effect of collection period variance (CPV), working capital investment policy (WCIP), and working capital financing policy (WCFP) on return on asset (ROA) among 113 property and construction sector companies listed in the Indonesian Sharia Stock Index (ISSI) over the period 2015-2024. Secondary data in the form of annual financial statements were obtained from the official website of the Indonesia Stock Exchange (IDX) and the respective company websites. The sample consists of 113 companies selected through purposive sampling, yielding a total of 601 observations using unbalanced panel data. Data were analyzed using panel data regression, with model selection conducted through the Chow Test and Hausman Test, resulting in the Fixed Effect Model as the chosen estimation approach. The findings indicate that CPV has a significant negative effect on ROA, suggesting that a wider gap between the speed of trade payables settlement and receivables collection is associated with lower firm profitability. WCIP has a significant positive effect on ROA, indicating that adequate current asset availability supports operational continuity and enhances profitability. WCFP has a significant negative effect on ROA, suggesting that excessive reliance on current liabilities as a financing source suppresses firm profitability. These findings imply that efficient and consistent working capital management is a key determinant in maintaining and improving the profitability of Sharia-compliant firms in Indonesia’s property and construction sector.